Sustainable Economic Performance in Kalimantan: A Perspective from Islamic and Conventional Banks—The Potential for Agricultural Financing and Financial Literacy - Niken Lestari; Wahab (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2026)
The island of Kalimantan, with its wealth of natural resources and strong agricultural and forestry sectors, is key to driving green economic development in Indonesia. This study develops a Data Envelopment Analysis model to measure sustainable economic performance in Kalimantan, focusing on the agricultural and forestry sectors. The potential for agricultural financing from commercial banks (conventional and Islamic banks), as well as regional banks (BPR and BPRS), is proposed as a driving factor for Sustainable Economic Performance, incorporating the moderating effect of financial literacy. This study utilises panel data from 55 regencies/cities on the island of Kalimantan for the period 2014–2023. The findings reveal that Sustainable Economic Performance on the island of Kalimantan is not yet efficient, with the highest level of Sustainable Economic Performance recorded in East Kalimantan Province and the lowest in South Kalimantan Province. Regression analysis results indicate that the potential for agricultural financing in Conventional Commercial Banks, Sharia Commercial Banks and Rural Banks (BPR) has a negative effect on Sustainable Economic Performance. However, the moderation of conventional and Sharia financial literacy successfully exerts a positive influence on the potential for agricultural financing in each of these banking sectors regarding Sustainable Economic Performance. Conversely, for Islamic Rural Banks (BPRS), no evidence was found of an influence of the potential for agricultural financing on Sustainable Economic Performance in Kalimantan, either before or after moderation by Islamic financial literacy. The research findings recommend that regulators provide substantial support for agricultural financing across various banking schemes and develop more integrated financial literacy enhancement programmes.